Alveolar bone loss associated to periodontal disease in lead intoxicated rats under environmental hypoxia - Terrizzi, Antonela Romina (2013)
Previously reported studies from this laboratory revealed that rats chronically intoxicated with lead (Pb) under hypoxic conditions (HX) impaired growth parameters and induced damages on femoral and mandibular bones predisposing to fractures. We also described periodontal inflammatory processes under such experimental conditions. Periodontitis is characterised by inflammation of supporting tissues of the teeth that result in alveolar bone loss. The existence of populations living at high altitudes and exposed to lead contamination aimed us to establish the macroscopic, biochemical and histological parameters consistent with a periodontal disease in the same rat model with or without experimental periodontitis (EP). Sixty female rats were divided into: Control; Pb (1000 ppm of lead acetate in drinking water); HX (506 mbar) and PbHX (both treatments simultaneously). EP was induced by placing ligatures around the molars of half of the rats during the 14 days previous to the autopsy. Hemi-mandibles were extracted to evaluate bone loss by histomorphometrical techniques. TNFα plasmatic concentration was greater (p < 0.01) in Pb and HX animals. TBA-RS content was significantly higher in gums of rats with or without EP only by means of Pb. The SMG PGE2 content increased by Pb or HX was higher in PbHX rats (p < 0.01). Pb and HX increased EP induced alveolar bone loss, while Pb showed spontaneous bone loss also. In conclusion, these results show that lead intoxication under hypoxic environment enhanced not only alveolar bone loss but also systemic and oral tissues inflammatory parameters, which could aggravate the physiopathological alterations produced by periodontal disease.